Kajian Anatomi Daun dan Morfologi Nepenthes spp. Koleksi Kebun Raya Baturaden Kabupaten Banyumas - Camelina Simbolon; Siti Samiyarsih; Wiwik Herawati (Fakultas Biologi Universitas Jenderal Soedirman, 2022)
Pitcher plant (Nepenthes spp.) is one of the carnivorous plants which is classified as unique, because of the pitch on the Nepenthes spp. is a modified leaf tip that changes its shape and function to become a trap for insects or other small animals. The Baturraden Botanical Garden is the areas used for the conservation of various plant species both ex-situ and in-situ including Nepenthes spp. This aim of this study is to 1) determine the leaf anatomy and morphology characters of Nepenthes spp. which grows in the Baturraden Botanical Garden area, 2) determine the different characters of each species of Nepenthes spp. which grows in the Baturraden Botanical Garden area based on leaf anatomy and morphology. The research was conducted by direct observation, purposive sampling method, taking leaf samples of Nepenthes spp. in the greenhouse of the Baturaden Botanical Garden. Observation of leaf anatomical characters by embedding method with 1% safranin staining. The results of the measurement of anatomical and morphological characters were analyzed using ANOVA at the 95% and 99% confidence level, then continued with tests of Least Significant Difference (LSD) and the result observation from the morphological observations were analyzed descriptively. The results showed that the eight Nepenthes species had the same anatomical structure consisting of cuticle, epidermis, and mesophyll tissue with varying sizes between species. The morphological characters of eight Nepenthes species varied among species with different sizes. The petiole is only owned by N. ampullaria, N. mirabilis, N. rafflesiana, the pitch that has a waist shape is only owned by N. mirabilis, N, gracilis, and N. tobaica, the most striking pitch color is N. rafflesiana. The differences in the leaf anatomy characters of the eight Nepenthes species were found in the stomata width, cuticle thickness, epidermal thickness, mesophyll thickness, leaf length, leaf width, leaf stalk, tendril length, pitch diameter, pitch shape, pitch color